Adjustment of girls in homemaking classes to family life - Essig, Mary, author; Morgan, David H., advisor; Williamson, Maude, committee member; Norton, Naoma, committee member; Hamilton, Olive F., committee member; Elliff, Rowan, committee member; Morgan, David H., committee member (Colorado State University. Libraries, 1945)
To view the abstract, please see the full text of the document.
Keywords: Girls; Women -- Employment; Parent and child